Socio-cultural history of Shupfomei Naga tribe : a historical study of Ememei , Leapana , and Paomata generally known as Mao-Poumai Naga tribe - Nepuni, William; Dena , Lal (Fwd.) (New Delhi, 2010)
The book, "A Socio-Cultural History of Shupfomei Naga Tribe" deals with the origin, migration and departure of the different Naga Tribes and particularly the four kindred Groups namely, Ememei, Lepaona, Paomata and Chuluve. In the past other Naga tribes knew these four groups as Shupfomei but today they are officially called the Mao and the Poumai tribes. The term "Shupfomei" was used in pre World War I era, followed by the decadence and the post-World War II, which witnessed the emergence of a new nomenclature called "Mao Naga Tribe". Initially, in the official record used by the Government of India, the term "Mao-Maram" was used. But slowly such a term "Mao-Maram" is much less used and though older generation did use it when making certain references in the office. Shupfomei Naga Tribe-concerning their Oral traditions, socio-cultural, socioreligious, socio-politics and socioeconomic life. And further more, their untold and unwritten history of Shupfomei Tribe expressed through dance, music, folktales, folksongs, etc. This Book Contains : - Introduction - Historical Background of Shupfomei Naga Tribe : Origin, Migration and Settlement - Socio-Cultural Life of Shupfomei - Shupfomei Feasts and Festivals - Shupfomei Traditional Religion - Shupfomei Socio-Cultural Change in the wake of Christianity and Education - General Conclusion. Changes are inevitable and yet even today the two tribes have much commonality in socio-cultural and historical background. No doubt this book will serve as an Eye opener to the future generation about their origin, migration and departure from Makhel. It is here future Research students will gain much.
Keywords: Naga tribe